Clinical findings after bioresorbable vascular scaffold implantation in an unrestricted cohort of patients with ST-segment elevation myocardial infarction (from the RAI registry). (1st May 2018) - Moscarella, Elisabetta; Ielasi, Alfonso; Varricchio, Attilio; De Angelis, Maria Carmen; Loi, Bruno; Tarantini, Giuseppe; Calabrò, Paolo; Cortese, Bernardo; Mazzarotto, Pietro; Gabrielli, Gabriele; Pisano, Francesco; Facchin, Michela; et al.
Abstract: Background: The bioresorbable vascular scaffold (BVS) technology may be an appealing option in ST-segment elevation myocardial infarction (STEMI) patients. However, the available evidence on its use in this challenging subset is limited. Methods: Registro Absorb Italiano (RAI) is a multicenter, prospective registry that aims to assess BVS performance through a 5-year follow-up of all consecutive patients who undergone at least 1 successful BVS implantation. As a part of it, a subgroup analysis in STEMI patients was performed and the outcomes of this cohort compared to the remaining population (defined as "non-STEMI") are reported here. Results: Among the 1505 patients enrolled, 317 (21.1%) had STEMI on admission. Among those, 232 (73.2%) underwent primary percutaneous coronary intervention (PCI) within 12 h from symptom onset; 64 (20.2%) were late-comers (>12 h); 16 (5%) underwent PCI after successful thrombolysis while 5 (1.6%) underwent rescue-PCI. At a median follow-up time of 12 months (IQR 6–20 months) no differences were noticed between STEMI and "non-STEMI" groups in terms of device-oriented composite endpoint (4.1% vs. 5.6%; p = 0.3) and its singular components: ischemia-driven target lesion revascularization (3.2% vs. 3.6%; p = 0.7), target-vessel myocardial infarction (3.2% vs. 2.8%; p = 0.7) and cardiac death (0.6% vs. 0.6%; p = 0.9). The rate of definite/probable scaffold thrombosis (ScT) was numerically higher but not significant in the STEMI group (2.5% vs. 1.3%; p = 0.1). Conclusions: BVS implantation in an unrestricted cohort of STEMI patients is associated with a numerically higher rate of ScT compared to the non-STEMI group. Further studies exploring the potential clinical impact of a pre-specified BVS implantation strategy in this high-risk clinical setting are needed. Highlights: Bioresorbable vascular scaffolds may be an appealing option in STEMI patients. The RAI registry included 1505 patients with at least 1 successful BVS implantation. A subgroup analysis in STEMI patients included in the RAI registry was performed. BVS in STEMI is associated with a higher rate of thrombosis compared to non-STEMI.